Economic Determinants of Growth Acceleration During Covid-19 Pandemic: A Comparative Study Between Indonesia, Thailand and Vietnam - Wicaksono, Raden Mas Try Ananto Djoko; Rinaldi, Rina Putri (Journal of Developing Economies, 2021)
This paper analyzes the determinants of economic growth acceleration in Indonesia, Thailand, and Vietnam. It aims to reveal Thailand's plausible explanations and Vietnam's development success compared to Indonesia during the COVID-19 pandemic. This research provides an in-depth study parallel to a case study by using comparable variables. It examines six determinants: natural resources, investment, population growth, social-culture, human resources, and political. The evidence exhibits Vietnam has better conditions in all determinants compare to Indonesia and Thailand. Lessons learned from its development experiences could improve Vietnam's successful strategy with previous outbreaks to impact the current economic development. Keywords: COVID-19 Pandemic, Economic Growth, International Political Economic JEL : A10, A11, B27, F13, F21, F5, F52